Investigation on Saprolitic Laterite Ore Reduction Process using Palm Kernel Shell Charcoal: Kinetics and Phase Transformation - Petrus, Himawan Tri Bayu Murti; Putera, Andreas Diga Pratama; Warmada, I Wayan; Nurjaman, Fajar; Astuti, Widi; Prasetya, Agus (Faculty of Engineering Universitas Indonesia, 2022)
The performance and kinetic of saprolitic laterite reduction using palm kernel shell charcoal and anthracite were studied. The anthracite coal represents the conventional high-grade carbon content matter, and palm kernel shell charcoal represents biomass-based reductant. The experiment was conducted at a temperature ranging from 800 ̊ C and 1000 ̊ C. XRD analysis was applied to observe phase transformation. For the kinetic study, two models, namely (1) Jander and (2) Ginstling-Brounhstein diffusion model, were applied. The mineral phase results indicated that both reductants yield Magnetite from Goethite in the laterite. The best fit model is obtained by the Jander model with the energy activation of 33.68 kJ/mol for anthracite reductant and 10.99 – 18.19 kJ/mol for palm kernel shell reductant, indicating that reduction is easier to occur using palm kernel shell.